Avaliação da atividade citotóxica de complexos fosfínicos de Ru(II) com ligantes mercaptos e aciltioureias - Ribeiro, Gabriel Henrique (Universidade Federal de São Carlos, 2020)
In this thesis, two series of new Ru-phosphine complexes containing mercapto or acylthiourea ligands were synthesized, characterized and assessed their cytotoxic activities. The first series is composed of five complexes of general formula [Ru(NS)(dphppy)(dppb)]PF6 (AMP1-AMP5) [dpphpy = diphenyl-2-pyridylphosphine, NS = 2-mercaptopyridine (pyS; AMP1), 2-thiazoline-2-thiol (tzdt; AMP2), 6-mercaptopyridine-3-carboxylic acid (mpca, AMP3), 2-mercaptopyrimidine (pySm, AMP4) and 4,6-diamino-2-mercaptopyrimidine (damp, AMP5); dppb = 1,4-bis(diphenylphosphino)butane]. In the second series, complexes present the general formula [Ru(OS)(dphppy)(dppb)]PF6 (SPPM2-SPPM6) [OS= N,N-(dimethyl)-N'-benzoylthiourea (dmbth; SPPM2), N, N-(diethyl)-N'-benzoylthiourea (debth, SPPM3), N,N-(dipropyl)-N'-benzoylthiourea (SPPM4), N,N-(dibutyl)-N'-benzoylthiourea (dbbth, SPPM5), N,N-(diphenyl)-N'-benzoylthiourea (dpbth, SPPM6)]. The complexes were characterized by elemental analysis, spectroscopic techniques (IR, UV/Visible, 1D and 2D NMR) and X-ray diffraction. In the characterization, the correlation between the phosphorous atoms with their respective aromatic hydrogens of the compounds in the assignment stands out, by 1H-31P HMBC experiments. The cytotoxic activity of the complexes was evaluated against cell lines derived from human tumors, MDA-MB-231 (breast cancer) and A549 (lung cancer) and against non-tumoral human cell lines derived from lung MCR-5 and breast MCF-10A. The compounds showed good to excellent anticancer activities against cancer cell lines, with IC50 values significantly lower than the free ligands and cisplatin. For A549 tumor cells, the complexes with mercaptos had IC50 values in the range of 0.12-2.59 µM, and the complexes with acylthiourea in the range of 0.10-0.98 µM. In the breast tumor cells, IC50 values were in the range of 0.08-0.36 µM and 0.25-1.05 µM for the AMP and SPPM series, respectively. All complexes were also selective for tumor cells in comparison to the respective non-tumoral cell lines. The complexes with acylthiourea showed expressive selectivity toward lung tumor cells, with selectivity indexes (SI) values above (or equal to) 10. The compounds AMP4 (SI= 6.7) and SPPM4 (SI= 33) were chosen for further studies in lung tumor cells, due to the better selectivity index in their respective series. Both complexes were able to inhibit colony formation and alter the morphology of tumor cells A549. In the cell cycle analysis of the cells, the complexes induced an accumulation of cells with abnormal content, called Sub-G1 cells, which represents the fraction of dead cells and fragmented DNA. The fragmentation of DNA is due to the cell apoptosis process, confirmed for cells treated with the AMP4. For A549 cells treated with the SPPM4 complex, possibly other cell death processes are involved. The possible biological targets of the complexes that could act as triggers for the cell death process were also studied. The complexes presented weak reversible interactions via minor groove of the DNA. The complexes caused no significant changes in the tertiary and secondary DNA structures, indicating that this biomolecule is probably not the primary target for them. Study with enzymatic target, especially targets overexpressed in tumor cells that justify the cytotoxic activity of the compounds were carried out. And it was found that the complexes are capable of partially inhibiting the Top IB catalytic activity, at low concentrations, close to the IC50 values of cancer cell lines. Overall, the proteasome enzyme can be a biological target for these complexes. The results indicate that ruthenium complexes containing mercaptos or acylthiourea present promising cytotoxic activities for the development of chemotherapeutics for the treatment of cancer. Among the complexes assayed in HEK293T-uGFP cells, complex AMP5 was able to diminish the proteasomal chymotrypsin-like activity to a greater extent, indicating that the proteasome 26S enzyme can be a biological target of the compound.
Evaluation of the cytotoxic activity of new Ru(II)-phosphine complexes with mercapto or acylthiourea ligands
Keywords: Complexo rutênio; DNA; HSA; Inibição proteassoma; Topoisomerase; Câncer de mama; Câncer de pulmão; Linhagem tumoral A549; Linhagem tumoral MDA-MB-231; MCF-10A; MRC-5; RMN de 31P; 2-difenilfosfinapiridina; DPPB; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::CAMPOS DE COORDENACAO; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA